2019
DOI: 10.3390/molecules24224134
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Controllable Logic Circuits Based on DNAzyme Activity

Abstract: Recently, DNA molecules have been widely used to construct advanced logic devices due to their unique properties, such as a simple structure and predictable behavior. In fact, there are still many challenges in the process of building logic circuits. Among them, the scalability of the logic circuit and the elimination of the crosstalk of the cascade circuit have become the focus of research. Inspired by biological allosteric regulation, we developed a controllable molecular logic circuit strategy based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…DNA-based feedback cascades can significantly enhance signal propagation for reactions where target DNA concentrations are low [2][3][4][5][6][7][8][9][10]; however, these feedback cascades have a tendency to be 'leaky'. Any small amount of circuit instability has the potential to be amplified into a large amount of nonspecific background signal [11][12][13][14][15]. Previous studies have shown the effective use of porous membranes to control CNA reactions and minimize nonspecific molecular interactions [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…DNA-based feedback cascades can significantly enhance signal propagation for reactions where target DNA concentrations are low [2][3][4][5][6][7][8][9][10]; however, these feedback cascades have a tendency to be 'leaky'. Any small amount of circuit instability has the potential to be amplified into a large amount of nonspecific background signal [11][12][13][14][15]. Previous studies have shown the effective use of porous membranes to control CNA reactions and minimize nonspecific molecular interactions [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] Compared with a monorail circuit, a dual-track circuit obviously increases the complexity of DNA strands which limits the expansion of DNA logic circuit. Second, the DNA strands used as inhibitory signals do not play a very specic or unique role in the DNA logic circuit, especially the XOR gate [49][50][51] in which the output suppression were realized by using complementary DNA strands as two different inputs. In this case, two complementary input DNA strands consume each other thus no output will be made.…”
Section: Introductionmentioning
confidence: 99%
“…In biological systems, the activity of the DNAzyme is also affected by its own structural changes. This feature is widely used to construct molecular logic gates [ 44 , 45 ], cascade logic circuits [ 46 , 47 ], and catalytic circuits [ 48 ]. In addition, expansive regulation [ 49 , 50 , 51 ] is a special way to regulate the catalytic activity of the DNAzyme that does not need to change the structure of DNAzyme.…”
Section: Introductionmentioning
confidence: 99%